A Virtual Lab As A Vehicle For Active Learning Through Distance Education - Kusmawan, Udan (Universitas Terbuka, 2022)
Through a distance education system, the teacher education program meets its challenges in the pedagogy of practical courses. Correspondingly, student-teachers face challenges in completing their practical courses due to professional and geographical constraints. The survey research results revealed the effectiveness of a virtual lab application in connecting the pedagogical approach to the student teacher's needs for practicum through implementing the Scalable Practicum. The results showed that the virtual lab promotes excellent facilitation for student-teachers conducting science Scalable Practicum in their limited circumstances. This study recommends further research on wider scopes and samples to receive more comprehensive pictures regarding the effectiveness of the virtual lab.